Erythema marginatum: an uncommon presentation of acute rheumatic fever in a Nigerian adolescent girl-a case report - Barakat Adeola Animasahun; Faith O. Lawani; Moriam Omolola Lamina (SpringerOpen, 2021)
Abstract Background Erythema marginatum is an uncommon presentation in children with acute rheumatic fever and it is one of the major criteria needed to make a diagnosis. It is seen in less than 10% of cases. It is also reported to be difficult to detect in black-skinned children. This is the first and only patient to present with the above since the inception of the unit about 14 years ago and also the first to be reported in Nigeria as far as the authors are aware, after a careful literature search; hence, we report this case based on the rarity of this symptom of acute rheumatic fever. Case presentation This is a case report of O.E, a 12-year-old Nigerian girl who presented with features of acute rheumatic fever, and these features included the rare manifestation of erythema marginatum. She presented with generalized skin eruptions on the trunk and extremities, sparing the face, migratory polyarthritis, features of congestive heart failure and high grade continuous fever. The skin lesions consisted of papules, patches, plaques and polycycles with a reticular pattern having serpiginous and raised borders. Diagnostic investigations revealed elevated erythrocyte sedimentation rate of 83mm/h, anti-streptolysin O titer of 2020IU/L and echocardiography which showed thickened mitral valves with grade II mitral regurgitation and a mild pulmonary artery hypertension. The patient was treated with anti-inflammatory and anti-failure drugs and commenced secondary prophylaxis with benzathine penicillin. Skin eruptions resolved within 3 weeks of management and are currently on follow up. Conclusions We present the above to increase awareness on the possibility of acute rheumatic fever presenting with erythema marginatum in our region, to encourage early diagnosis of acute rheumatic fever to reduce morbidity and mortality from its sequel, rheumatic heart disease.